The Effect of the Effectiveness of E-Filing Implementation on Tax Compliance of MSMEs in Greater Solo - Harimurti, Fadjar; Rispantyo; Nuralamsah, Muhammad (Jurnal Economic Resource, 2025)
The innovation of electronic tax return reporting through e-filing aims to improve taxpayer compliance. However, in practice, the implementation of e-filing has not been effective, mainly due to various obstacles such as a lack of taxpayer knowledge, low digital literacy, and minimal socialisation regarding the use of e-filing. In addition, the implementation of e-filing is not yet fully automated (full automation). This phenomenon is also felt by Micro, Small, and Medium Enterprises (MSMEs) in the Greater Solo area. Therefore, this study aims to analyse the effect of the effectiveness of e-filing implementation on tax compliance among MSMEs in Solo. The population in this study consisted of 11,157 MSMEs, with a sample of 386 MSMEs obtained using the Slovin formula. The data used are primary data collected through the distribution of questionnaires. Data analysis techniques use the Structural Equation Modelling–Partial Least Square (SEM-PLS) method with the assistance of SmartPLS version 3 software. The analysis results show that the effectiveness of e-filing implementation has a positive and significant effect on MSME tax compliance in Solo Raya.